Interfacial Electrofabrication of Freestanding Biopolymer Membranes with Distal Electrodes - Hu, Piao (Langmuir : the ACS journal of surfaces and colloids, 2020)
Using electrical signals to guide materials' deposition has a long-standing history in metal coating, microchip fabrication, and the integration of organics with devices. In electrodeposition, however, the conductive materials can be deposited only onto the electrode surfaces. Here, an innovative process is presented to electrofabricate freestanding biopolymer membranes at the interface of electrolytes without any supporting electrodes at the fabrication site. Chitosan, a derivative from the naturally abundant biopolymer chitin, has been broadly explored in electrodeposition for integrating biological entities onto microfabricated devices. It is widely believed that the pH gradients generated at the cathode deprotonate the positively charged chitosan chains into a film on the cathode surface. The interfacial electrofabrication with pH indicators, however, demonstrated that the membrane growth was driven by the instantaneous flow of hydroxyl ions from the ambient alginate solution, rather than the slow propagation of pH gradients from the cathode surface. This interfacial electrofabrication produces freestanding membrane structures and can be expanded to other materials, which presents a new direction in using electrical signals for manufacturing